The Cardiovascular Reserve Index—A Noninvasive Clinical Insight Into Heat Intolerance. Issue 3 (May 2021) - Schiffmann, Nathan; Schermann, Haggai; Mazgaoker, Savyon; Shaulov, Yafim; Gabbay, Uri; Epstein, Yoram; Yanovich, Ran
Abstract : Objective: To noninvasively explore the heat intolerance condition during exercise-heat stress by assessing cardiovascular (CV) performance. Design: Prospective study of participants undergoing a standard heat-tolerance test (HTT). Setting: Institutional study. Participants: Ninety-five young males: 16 heat-intolerant (HI) and 79 heat-tolerant (HT). Interventions: Cardiovascular performance during an HTT was estimated by heart rate (HR) and blood pressure measurements. Main Outcome Measures: The sensitivity of the cardiovascular reserve index (CVRI) and the dynamic heart rate reserve (dHRR) index to predict heat intolerance was compared. Results: A significant difference in the CV reserve during exercise-heat stress was exhibited between the HI and the HT groups. Starting at a similar level, the reduction in the CV reserve at HTT endpoint was much greater in the HI than the HT individuals ( P < 0.0001), as depicted by both the CVRI and the dHRR. This result indicates a greater utilization of the CV reserve by HI individuals. The CVRI is likely to be better predictor of heat intolerance than the dHRR because the partial area under the curve in the high sensitivity (>90%) region of its receiver operating characteristic curve is higher (93.2 vs 76.8). Conclusions: More than being a predictor, the CVRI may provide a new clinical insight into heat intolerance because it noninvasively characterizes the efficiency of an individual's thermoregulatory mechanism and hints that an impaired CV reserve might underlie heat intolerance. The CVRI provides a noninvasive measurement of thermoregulation, which has been long awaited to enable on-field studies and dynamic monitoring of heat-exposed task forces.